Scientific approaches to the definition of the concept «tourism destination» - Nassanbekova, S.T.; Uruzbayeva, N.A.; Rodríguez Zapatero, M. (BUKETOV BUSINESS REVIEW, 2019)
In this article the various approaches to the definition of the concept «tourist destination» are discussed. Although, it is one of the most frequently used terms in the analysis of tourism, currently, it cannot be stated that there is one generally accepted definition or even an approach to this term. As the subject of analysis of many different sciences, including economic, geographical, sociological sciences, this term is understood differently. The authors analyzed the main economic and geographical scientific approaches, their features and applicability for economic analysis. The article discusses and analyzes classical spatial or geographical approaches, economic approaches which, in turn, are divided into: a) management-oriented or in terms of supply; b) customer-oriented in terms of demand; c) systemic, neoinstitutional or network approaches that become popular in recent years. The proposed separation of approaches to the definition of the term or concept of «tourist destination» is very conditional and non-exhaustive; the boundaries of the various approaches are often blurred. Despite of the fact that the study focuses on an approach that is more appropriate for economic analysis, it should be borne in mind that the tourist destination is still an interdisciplinary problem.